2010
DOI: 10.1016/j.mri.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolism and cognitive impairment in HIV infection: a 3-T magnetic resonance spectroscopy study

Abstract: Background and Purpose HIV-associated dementia (HAD) has been extensively studied using magnetic resonance spectroscopy (MRS) at field strengths of 1.5 Tesla (T). Higher magnetic field strengths (such as 3T) allow for more reliable determination of certain compounds, such as glutamate (Glu) and glutamine (Gln). The current study was undertaken to investigate the utility of 3T MRS for evaluating HIV+ patients with different levels of cognitive impairment with emphasis on the measurement of Glu and Glx (the sum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
4
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 31 publications
6
58
4
1
Order By: Relevance
“…In a previous report describing CMRs quantified using the LCmodel in HIV disease at a higher magnetic field strength than our study, 24 mean CMRs in the FWM were 1.28, 0.32 and 0.56 for NAA/Cr, Cho/Cr and mI/Cr, respectively. These values are similar to our findings in the FWM utilizing the TARQUIN package (1.25, 0.28 and 0.91 for NAA/Cr, Cho/Cr and mI/Cr, respectively) and differed to our findings utilizing the jMRUI package (1.76, 1.05 and 1.05 for NAA/Cr, Cho/Cr and mI/Cr, respectively).…”
Section: Discussioncontrasting
confidence: 43%
“…In a previous report describing CMRs quantified using the LCmodel in HIV disease at a higher magnetic field strength than our study, 24 mean CMRs in the FWM were 1.28, 0.32 and 0.56 for NAA/Cr, Cho/Cr and mI/Cr, respectively. These values are similar to our findings in the FWM utilizing the TARQUIN package (1.25, 0.28 and 0.91 for NAA/Cr, Cho/Cr and mI/Cr, respectively) and differed to our findings utilizing the jMRUI package (1.76, 1.05 and 1.05 for NAA/Cr, Cho/Cr and mI/Cr, respectively).…”
Section: Discussioncontrasting
confidence: 43%
“…NAA was also found to increase after initiation of cART 6, 46 . Previous 3T studies have also reported decreasing Glx concentrations (or Glx/Cr ratios) with increasing symptomatology in HIV infection 17, 18 , and decreased levels compared to HIV− controls 19 . Although some 3T studies have used the technique of TE-averaged PRESS 19 to selectively detect Glu, generally it can be difficult to reliably separate Glu and from Gln using conventional MRS.…”
Section: Discussionmentioning
confidence: 73%
“…MR spectroscopic imaging (MRSI) studies also performed at long TE found progressive declines in NAA from HIV− controls, to asymptomatic and then symptomatic HIV+ patient groups in multiple gray and white matter regions 6, 18, 46 . NAA was also found to increase after initiation of cART 6, 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic Resonance Spectroscopy. MR imaging and spectroscopy were performed on a 3-T Philips Intera scanner with a six-channel SENSE head coil as previously described (53). Spectra were analyzed using the LCModel algorithm (54) and quantified in millimolar concentrations using the unsuppressed water signal as an internal intensity reference.…”
Section: Methodsmentioning
confidence: 99%